Elastic monumentality? The Stone Mountain Confederate Memorial and counterpublic historical space. (4th March 2019) - Autry, Robyn
ABSTRACT: Can blatantly racist-nationalist imageries that are literally carved into stone be recast as inclusionary? Can it be 're-seen' without being remodeled? By whose eyes and under what conditions? This essay examines the uneven development of the Stone Mountain Confederate Memorial in the United States. It questions how the impulse to memorialize in the aftermath of war and then re-memorialize relates to conflicts over the legacies of US slavery and the Civil War. Increasingly, these struggles over representations of divisive histories are waged alongside a growing heritage tourist industry and in the context ongoing racial conflict.